A Two-State Study of Family Child Care Engagement in Quality Rating and Improvement Systems: A Mixed-Methods Analysis. Issue 6 (18th August 2017) - Hallam, Rena; Hooper, Alison; Bargreen, Kaitlin; Buell, Martha; Han, Myae
ABSTRACT: Research Findings . The current study is a mixed-methods investigation of family child care provider participation in voluntary Quality Rating and Improvement Systems (QRIS) in 2 states. Study 1 is an analysis of matched QRIS and child care licensing administrative data extracted from both states in May, 2014. Poverty and population density variables were added to the dataset by aligning U.S. Census data and Rural Urban Commuting Area codes (RUCA) to the matched state child care data. Participation patterns differed in the 2 states relative to provider characteristics (subsidy receipt, years licensed, and location). Study 2 consists of focus groups with participating ( n = 22) and non-participating ( n = 19) providers. Professionalism and financial incentives emerged as significant in attracting family child care providers to QRIS. Although family child care providers identified several clear benefits to QRIS, many more challenges emerged that negatively impact their participation. Practice or Policy . As most states are employing a QRIS framework to integrate quality improvement efforts, perspectives from this sector of early care and education are often overlooked. Study findings suggest that QRIS can be more responsive and effective with family child care providers if more consideration of their unique features are considered in systems design and implementation.